The implication of agricultural land-use change on food security in Benue state, Nigeria - Ihemezie, Eberechukwu Johnpaul; Onunka, Cynthia Nneka; Umaru, Ibrahim Isaac (Journal of Tropical Agriculture, 2020)
This study employed geo-physical Land Use Land Cover (LULC) satellite data and crop yield data to examine the trend of agricultural land-use change and how it affected food security in the Nigerian state of Benue. Satellite imageries were downloaded for the years 1980, 1990, 2000, 2010, and 2015 from the United States Geological Survey (USGS) website, while crop yield data from 1980 to 2015 were obtained from the Benue State Ministry of Agriculture. Satellite image datasets were analyzed using remote sensing and GIS techniques, and data extracted for a quantitative analysis while crop yield data and data on percentage changes in cropland/vegetation were analyzed using regression analysis. The results of the study showed that the trend of agricultural land-use change in Benue state, Nigeria is tending towards reduction in agricultural lands. While this negative trend was found to reduce the output of some crops (e.g. yam, maize and groundnut), it seemed to have also spurred an increase in the production of other crops with more economic value (e.g. rice and cassava) due to intensification. The study recommends that appropriate landuse policies should be put in place to prevent unguarded loss of agricultural lands so as to forestall looming food security crisis.